Criminological Review of Juvenile Delinquency in Society Due to Parenting in the Gen Z Era - Junus, Irabiah; AM, Muhammad As Ari.; Yahyanto, (Journal of Law and Legal Reform, 2025)
This study examines the phenomenon of juvenile delinquency in society with a focus on the influence of parenting patterns in the Generation Z (Gen Z) era. Juvenile delinquency, which includes deviant behavior and criminal acts, is increasingly complex along with technological developments and social change. Parenting patterns applied by parents, whether autocratic, permissive, responsive, or neglectful, contribute significantly to adolescent behavior. This research method involves literature analysis and surveys of adolescents and parents to understand the relationship between parenting patterns and delinquent behavior. The results show that responsive parenting patterns and parental involvement in children’s lives are positively related to good social behavior, while permissive or neglectful parenting patterns have the potential to increase the risk of delinquency. This study suggests the need for parent education programs and community involvement to create an environment that supports positive development for adolescents in the Gen Z era. By understanding the interaction between parenting patterns and adolescent behavior, it is hoped that effective prevention strategies can be produced to overcome juvenile delinquency in society.